A Review of Clinical and Preclinical Studies on the Therapeutic Potential of Black Seeds (Nigella sativa) in the Management of Polycystic Ovarian Syndrome (PCOS) - Rajkapoor Balasubramanian; Naina Mohamed Pakkir Maideen; Sudha Muthusamy; Mirunalini Gobinath (Korean Pharmacopuncture Institute, 2023)
Objectives: Polycystic ovary syndrome (PCOS) is a condition that occurs frequently among women of reproductive age and is a polygenic, multifactorial, endocrine, and metabolic disorder. PCOS is becoming more common as a result of risk factors such as current lifestyle, overnutrition, and stress. The use of traditional herbal medicine is higher among the global population. Hence, this review article focuses on the potential of Nigella sativa to manage women with PCOS.Methods : : A literature search was carried out using databases including Medline, Google Scholar, EBSCO, Embase, and Science Direct, as well as reference lists, to identify relevant publications that support the use of N. sativa in the management of women with PCOS.Results : : Several clinical and preclinical studies have demonstrated that the major bioactive constituent of black seed (N. sativa), thymoquinone, has potential for managing women with PCOS. Moreover, N. sativa may help to manage oligomenorrhea and amenorrhea in women with PCOS through its anti-inflammatory and antioxidant properties.Conclusion : : N. sativa has potential for use as a herbal medicine for managing women with PCOS as an integrative medicine along with traditional and modern medicine in conjunction with calorie restriction and regular exercise.